ON THE BREAKING OF GENERATED WAVES RUNNING IN STILL WATER - Kusumawinahyu, W.M. Kusumawinahyu (MATEMATIKA, 2011)
This research is motivated by the requirement of hydrodynamics laboratories to generate extreme waves for testing ships in steep, large amplitude wave fields. For this purpose, finding criteria that determine if wave breaking will occur is important. Different from initial value problems, in this contribution we will consider the signaling problem: a time signal is prescribed to a wave maker in a wave tank that produces propagating waves running in initially still water. The aim is to observe the resulting nonlinear effects on the waves and to study in which cases the waves will or will not break. This also leads to a threshold value for generated waves, and, moreover, to the location in the tank where wave breaking may occur. To study this, we consider Bichromatic waves and Benjamin Feir-waves, and investigate the evolution by using a numerical simulation code HUBRIS developed by Westhuis; the validity of this code has been tested against laboratory experiments. The result of our investigations is that for both classes the parameters of wave breaking are more extreme in the signaling case than in the case of initial value problem.